1983
DOI: 10.1002/1097-0142(19831015)52:8<1369::aid-cncr2820520806>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of monoclonal antibodies leu 1 and OKT1 with malignant human lymphoid cells. Correlation with conventional cell markers

Abstract: This study delineated the distribution of reactivity of malignant human lymphoid cells with monoclonal antibodies Leu 1 and OKT1, and correlated this expression with that of conventional lymphoid cell markers. The presence of Leu 1 on benign lymph nodal T‐cells and its absence from benign lymph nodal B‐cells was confirmed. Twenty‐two T‐cell neoplasms, expressing a variety of intrathymic and mature peripheral phenotypes, expressed Leu 1, but this expression was heterogeneous with respect to percent‐positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 24 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…An association between CALLA positive cases and the absence of Ti expression has been suggested previously,'" 1833 although others have reported a variable expression of Leul/OKT1 positive cells in follicular lymphomas.34 35 In conclusion, the results of this study suggest that, even with a limited range of immunological investigations, some consistency in classification of disease may be attained. The phenotypic pattern represented by most cases of CLL was clearly shown to be: low density SIg; increased expression of MRBC receptors; the presence of membrane TU1, and, finally, the absence of significant CALLA and FMC7.…”
Section: Discussionsupporting
confidence: 71%
“…An association between CALLA positive cases and the absence of Ti expression has been suggested previously,'" 1833 although others have reported a variable expression of Leul/OKT1 positive cells in follicular lymphomas.34 35 In conclusion, the results of this study suggest that, even with a limited range of immunological investigations, some consistency in classification of disease may be attained. The phenotypic pattern represented by most cases of CLL was clearly shown to be: low density SIg; increased expression of MRBC receptors; the presence of membrane TU1, and, finally, the absence of significant CALLA and FMC7.…”
Section: Discussionsupporting
confidence: 71%
“…Representative portions of 91 lymph nodes and 26 ocular adnexal lymphoid neoplasms were freshly obtained under sterile conditions from the surgical specimens of patients undergoing evaluation for possible malignant lymphoma. The lymph node biopsies were classified by conventional histopathologic criteria as non-Hodgkin's lymphoma (5 l), benign lymphoid hyperplasia (25) or Hodgkin's disease ( 15). The ocular adnexal biopsies were classified as benign lymphoid hyperplasia ( 10) or non-Hodgkin's lymphoma (16) according to previously published histopathologic criteria."…”
Section: Specimensmentioning
confidence: 99%
“…The assessment of monoclonal light chain immunoglobulins in cells suspensions, aspirates and tissue sections of lymph nodes and blood lymphocytes has been made possible by immunofluorescent microscopy, flow cytometry and immunocytology. Studies of B-non-Hodgkin's lymphomas of low and high malignancy using suspension immunofluorescence of lymph node cells with polyclonal antibodies (Aisenberg et al 1983;Cossman et al 1984;Knowles et al 1983) and irnmunocytological investigation of lymph node aspirates with a monoclonal antibody (Oertel et al 1988) demonstrated that the majority of B-lymphomas showed monoclonal light chain immunoglobulins. Immunohistological studies of frozen sections of B-cell lymphomas of low malignancy using polyclonal antibodies showed in the majority of cases the monotypie of the light chains.…”
Section: Discussionmentioning
confidence: 99%